Diffusivities and atomic mobilities in bcc TiNbTa alloys. (June 2019) - Bai, Weimin; Xu, Guanglong; Yang, Zhijie; Liu, Libin; Zhang, Ligang; Zeng, Lijun; Wu, Di
Abstract: β-type titanium alloys have been extensively studied by researchers as the promising biomedical materials due to their superior performance. Nb and Ta are candidate elements that can reduce the modulus and enhance the strength of the titanium alloy while stabilizing the β phase. It is crucial to study the diffusion phenomenon in β -TiNbTa alloy for understanding the microstructure evolution in production process and developing new alloys. In this work, the inter- and impurity diffusion coefficients in β -TiNbTa alloy were determined using diffusion couple technique combined with Whittle-Green and Hall methods. Based on thermodynamic description, the atomic mobilities in bcc phase in TiNbTa system were obtained by assessing the experimental data using CALPHAD (CALculation of PHAse Diagrams) method. In the optimizing procedure, the end member and the binary description for TiTa and TiNb were reassessed. A self-consistent atomic mobility database for bcc phase in TiNbTa system was developed and examined by comparing the calculated diffusion coefficient with the experimental results. Simulations of the diffusion couple were also implemented by DICTRA module in Thermo_Calc software to evaluate the accuracy of the parameters. Highlights: The interdiffusion and impurity coefficients in bcc Ti-Nb-Ta alloys were obtained using Whittle-Green and Hall method. An atomic mobility database was developed using CALPHAD method. End members and binary parameters for binary Ti-Ta and Ti-Nb systems were reassessed. Calculations and simulation were proceeded to examine the accuracy of the parameters.